2007
DOI: 10.1901/jeab.2007.80-06
|View full text |Cite
|
Sign up to set email alerts
|

Tests of Behavioral‐economic Assessments of Relative Reinforcer Efficacy: Economic Substitutes

Abstract: This experiment was conducted to test predictions of two behavioral-economic approaches to quantifying relative reinforcer efficacy. According to the first of these approaches, characteristics of averaged normalized demand curves may be used to predict progressive-ratio breakpoints and peak responding. The second approach, the demand analysis, rejects the concept of reinforcer efficacy, arguing instead that traditional measures of relative reinforcer efficacy (breakpoint, peak response rate, and choice) corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 35 publications
1
33
2
Order By: Relevance
“…Although intensity of demand has been found to be among the most highly correlated with alcohol-related problems and symptoms of alcohol use disorders (Murphy & MacKillop, 2006; MacKillop et al, 2010), other indices of demand were found to be better predictors of treatment response for heavy alcohol use (MacKillop & Murphy, 2007). In general these results provide further evidence that reinforcement value is not a homogenous construct (Bickel et al, 2000; Johnson & Bickel, 2006; Madden et al, 2007), and that the different dimensions of reinforcement generated by demand curves may have unique associations with clinically relevant phenomena such as motivation and dependence.…”
Section: Discussionmentioning
confidence: 62%
“…Although intensity of demand has been found to be among the most highly correlated with alcohol-related problems and symptoms of alcohol use disorders (Murphy & MacKillop, 2006; MacKillop et al, 2010), other indices of demand were found to be better predictors of treatment response for heavy alcohol use (MacKillop & Murphy, 2007). In general these results provide further evidence that reinforcement value is not a homogenous construct (Bickel et al, 2000; Johnson & Bickel, 2006; Madden et al, 2007), and that the different dimensions of reinforcement generated by demand curves may have unique associations with clinically relevant phenomena such as motivation and dependence.…”
Section: Discussionmentioning
confidence: 62%
“…One explanation for the lack of treatment differences in maximum price is that it does not account for differences in the level of food consumption or expenditure, which were the main differences between the ewes with different BCS. Other studies found maximum expenditure to be a more reliable indicator of motivation than maximum price (Madden et al, 2007a(Madden et al, , 2007b, and maximum expenditure may therefore be a more suitable indicator of motivation for food in animal studies. The approach speed of the first visit to the feeding station was slower in HBC ewes, another indication that feeding motivation was low.…”
Section: Discussionmentioning
confidence: 92%
“…If so, these findings seem at variance with much of the literature that suggests for the most part that larger doses are preferred (see "Introduction" for references). We suggest that responding on FR schedules and this hold-down schedule do not seem to provide a clear measure of efficacy (or effectiveness or preference) and that it probably does not make sense to find one simple metric of this measure (see e.g., Katz 1990;Madden et al 2007 for discussion). Rather, these schedule conditions may be more useful to explore other issues related to drug-taking, such as the regulation of drug intake.…”
Section: Discussionmentioning
confidence: 92%